2018
DOI: 10.1021/acs.energyfuels.7b02473
|View full text |Cite
|
Sign up to set email alerts
|

Emission Modeling of an Interturbine Burner Based on Flameless Combustion

Abstract: Since its discovery, the flameless combustion (FC) regime has been a promising alternative to reduce pollutant emissions of gas turbine engines. This combustion mode is characterized by well-distributed reaction zones, which potentially decreases temperature gradients, acoustic oscillations, and NOx emissions. Its attainment within gas turbine engines has proved to be challenging because previous design attempts faced limitations related to operational range and combustion efficiency. Along with an aircraft co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
1
30
0
Order By: Relevance
“…When temperature, velocity direction, Y CH4 and Y H2O are employed as clustering criteria, the NO x trend obtained with GRI 2.11 reaction mechanism is monotonic and its slope is the opposite of the experimental data: condition a had the highest NO x value. For GRI 3.0, overall values are higher than those of GRI 2.11 (a behavior previously reported by Perpignan et al, 2018b), but condition a has a lower value than condition b, making the overall trend non-monotonic. The values, however, are not in good agreement with experiments for both chemical reaction mechanism.…”
Section: Agnes Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…When temperature, velocity direction, Y CH4 and Y H2O are employed as clustering criteria, the NO x trend obtained with GRI 2.11 reaction mechanism is monotonic and its slope is the opposite of the experimental data: condition a had the highest NO x value. For GRI 3.0, overall values are higher than those of GRI 2.11 (a behavior previously reported by Perpignan et al, 2018b), but condition a has a lower value than condition b, making the overall trend non-monotonic. The values, however, are not in good agreement with experiments for both chemical reaction mechanism.…”
Section: Agnes Resultsmentioning
confidence: 49%
“…The adoption of EGR might cause the required conditions for FC to occur, as O 2 concentrations drop and initial temperatures rise. Studying FC, the work of Perpignan et al (2018b) showed the results of a CRN manually built based on CFD made with the Flamelet Generated Manifolds (FGM) approach, which is also employed in the present work. The authors achieved better agreement with CO and NO x experimental data using the CRN than with the reacting CFD.…”
Section: Crns For Emission Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of NO x was quite successfully modeled in laboratory flames (Bergmann et al, 1998;Barlow et al, 2000) and in a small-scale MILD combustor (Veríssimo et al, 2011). The joint CFD-CRN method was also employed to predict NO x emissions in a interturbine flameless combustor for gas turbines: the flamelet generate manifolds (FGM) method was used to model the combustion process in the CFD simulation, whereas a detailed mechanism was considered in the resolution of the network of PSRs (Perpignan et al, 2018b). Although the CRN approach can be used to evaluate the variation of NO x emissions under different operating conditions in a cost-effective way, the reliability of the CRN predictions is strongly dependent on the accuracy of the underlying CFD simulation.…”
Section: Cfd Modeling Of No X Emissions In Mild Conditionsmentioning
confidence: 99%
“…CRN had shown the dominant pathway for NOx formation was the prompt NOx mechanism. In addition, they made some suggestions for improving the design by modifying the mixing ratios (Perpignan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%